Scraping the demos. Digitalization, web scraping and the democratic project. Issue 3 (2nd April 2020) - Ulbricht, Lena
ABSTRACT: Scientific, political and bureaucratic elites use epistemic practices like "big data analysis" and "web scraping" to create representations of the citizenry and to legitimize policymaking. I develop the concept of "demos scraping" for these practices of gaining information about citizens (the "demos") through automated analysis of digital trace data which are re-purposed for political means. This article critically engages with the discourse advocating demos scraping and provides a conceptual analysis of its democratic implications. It engages with the promise of demos scraping advocates to reduce the gap between political elites and citizens and highlights how demos scraping is presented as a superior form of accessing the "will of the people" and to increase democratic legitimacy. This leads me to critically discuss the implications of demos scraping for political representation and participation. In its current form, demos scraping is technocratic and de-politicizing; and the larger political and economic context in which it takes place makes it unlikely that it will reduce the gap between elites and citizens. From the analytic perspective of a post-democratic turn, demos scraping is an attempt of late modern and digitalized societies to address the democratic paradox of increasing citizen expectations coupled with a deep legitimation crisis.